PENGARUH FAKTOR RISIKO KECURANGAN, GOOD GOVERNMENT GOVERNANCE DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA ORGANISASI BERDASARKAN PENDEKATAN VALUE FOR MONEY : Studi pada Satuan Kerja Perangkat Daerah di Kabupaten Subang - Meiyanti, Fajar; Icih, Icih; Eka Putri, Trisandi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
The study intended to determine how the effects of fraud risk factors, good government governance and organizational citizenship behavior toward performance based on value for money approach. The population used in this research is 60 Satuan Kerja Perangkat Daerah (SKPD) in Subang Regency's Government. The sample size determination is based on the Slovin formula with 5 persen error rate. The method of sampling in this study is by proportionate stratified random sampling method. The sample used in this research is 52 samples. The analytical tool used in this research is multiple regression and hypothesis test using t-test and f test by using IBM SPSS Statistics 22. The result of the research showed that fraud risk factors had a negative effect not significant to the performance of value for money, good government governance has a significant positive effect on value for money performance and organizational citizenship behavior have no significant positive effect on value for money performance.